The crosstalk between STAT3 and microRNA in cardiac diseases and protection - Wu, Lan; Li, Zhizheng; Li, Yanfei (Frontiers in Cardiovascular Medicine, 2022)
Signal transducer and activator of transcription 3 (STAT3), an important transcription factor and signaling molecule, play an important role in cardiac disease and protection. As a transcription factor, STAT3 upregulates anti-oxidative and anti-apoptotic genes, but suppresses anti-inflammatory and anti-fibrotic genes in cardiac disease and protection. As a signaling molecule, STAT3 is the downstream or upstream of other molecule for signaling transduction, also activated in cardiac disease and protection. MicroRNAs (miRNAs) are endogenous short non-coding RNAs that regulate mRNA expression at the transcriptional level and prevent protein translation. Recently, STAT3 is reported to be not only the target of miRNA, but also the inhibitor or inducer of miRNA to modify the mRNA expression profiles in cardiomyocytes result in different effects in cardiac disease and protection. We summarize the current knowledge on STAT3 regulation of individual miRNAs and the modulation of STAT3 by miRNAs in cardiac diseases and protection.